Lithium ions removal from groundwater using waste-derived date pits modified with manganese oxide and cellulose nanocrystals - Hadeel A. Al-Karablieh (22302787) (2025)
Lithium (Li+) has been detected in water sources as a result of growing industrial activities, posing potential risks to both environmental and human health. To address this concern, the current investigation aimed to assess the feasibility of removing lithium ions from groundwater through adsorption using a novel waste-based adsorbent derived from date pits. The modification of date pits involved incorporating manganese oxide/cellulose nanocrystal (CNC) composites (MnO2/CNC@DP). Various parameters of the adsorption study were assessed, including pH, temperature, and the initial concentration of Li+, using both synthetic solutions and real groundwater samples. The adsorbent's physicochemical properties were characterized using a range of analytical techniques. The adsorption studies revealed that at pH 2, the Li+ removal efficiency reached 25.18 % and the adsorption capacity improved with higher initial Li+ concentrations, reaching 15.5 mg/g. Thermodynamic analysis indicated that the adsorption process was spontaneous and endothermic, with the Langmuir model providing the best fit to the experimental data. An efficiency of 88.42 % was achieved for the removal of Li+ from real groundwater samples. Desorption experiments further indicated that Li+ could be effectively desorbed using 1.0 M HCl. The proposed mechanisms governing Li+ adsorption by (MnO2/CNC@DP) included chemisorption, pore filling, intra-particle diffusion, and electrostatic attraction. In conclusion, this study demonstrates that MnO2/CNC@DP is a promising and cost-effective adsorbent for removing Li+ from contaminated groundwater. Other Information Published in: Groundwater for Sustainable Development License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.gsd.2025.101544